Testing for ARCH in the presence of nonlinearity of unknow form in the conditional mean - Andrew P. Blake; George Kapetanios (Queen Mary University of London, Department of Economics, 2003)
Tests of ARCH are a routine diagnostic in empirical econometric and financial analysis. However, it is well known that misspecification of the conditional mean may lead to spurious rejections of the null hypothesis of no ARCH. Nonlinearity is a prime example of this phenomenon. There is little work on the extent of the effect of neglected nonlinearity on the properties of ARCH tests. This paper provides some such evidence and also new ARCH testing procedures that are robust to the presence of neglected nonlinearity. Monte Carlo evidence shows that the problem is serious and that the new methods alleviate this problem to a very large extent.
Keywords: C12; C22; C45; 330; Nonlinearity; ARCH; Neural networks; ARCH-Modell; Neuronale Netze; Nichtlineares Verfahren